Metal-organic framework-derived ZrO2/NiCo2O4/graphene mesoporous cake-like structure as enhanced bifunctional electrocatalytic cathodes for long life Li-O2 batteries - Palani, Raja; Wu, Yi–Shiuan; Wu, She–Huang; Jose, Rajan; Yang, Chun–Chen (Elsevier Ltd, 2022)
Metal-organic frameworks (2D MOFs) have great potential to improve the electrochemical performance of Li-O2 batteries with high O2 accessibility, the catalytic activity of the open active metal sites, and large specific surface areas. Herein, we prepared a 3D hierarchical ZrO2@NiCo2O4/GNS (ZNCO) framework as cathode catalysts in Li-O2 batteries that have been developed to synthesize with Zr/Ni to Co molar ratio of 0.1:1:2 by a facile hydrothermal method. The coating of foreign Zr4+ ions into the nickel cobaltite matrix, have superior oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) bifunctional activity, and allowed the formation of 3D dimensional networks for oxygen diffusion, electrolyte impregnation, and has very ORR/OER low overpotential due to Zr insertion. Moreover, the ZrO2 coated shell increases the electronic conductivity, porosity, specific surface area, and protects the core and interstitial decoration against lithium peroxide passivation (Li2O2). The electrochemical performance of the 3D hierarchical ZrO2@NiCo2O4/GNS nanocomposite delivers a higher discharge capacity of 9034 mAh g–1 at 50 mA g–1 and a superior cycling performance up to 100 cycles with a limited capacity of 1000 mAh g−1 at 100 mA g−1. An ORR/OER mechanism was suggested to illustrate the interesting growth of spherical-like particle and film-like Li2O2 deposits at the different cycles for the ZrO2@NiCo2O4/GNS cathodes. Such MOF-derived; hierarchical porous nanocomposites can lead to high-performance efficient bifunctional electrocatalysts and enables the formation and decomposition of discharge products (Li2O2) during the discharge-charge process.